Relationship between multimorbidity and physical activity: Secondary analysis from the Quebec health survey - Soubhi Hassan; Hudon Catherine; Fortin Martin (BMC, 2008)
Abstract Background Abundant literature supports the beneficial effects of physical activity for improving health of people with chronic diseases. The relationship between multimorbidity and physical activity levels, however, has been little evaluated. The purpose of the current exploratory study was to examine the relationship between a) multimorbidity and physical activity levels, and b) long-term limitations on activity, self-rated general health, psychological distress, and physical activity levels for each sex in adults, after age, education, income, and employment factors were controlled for. Methods Data from the Quebec Health Survey 1998 were used. The sample included 16,782 adults 18-69 yr of age. Independent variables were multimorbidity, long-term limitations on activity, self-rated general health, and psychological distress. The dependent variable was physical activity levels. Links between the independent and dependent variables were assessed separately for men and women with multinomial regressions while accounting for the survey sampling design and household clustering. Results About 46% of the participants were men. Multimorbidity was not associated with physical activity levels for either men or women. Men and women with long-term limitations on activity and with poor-to-average self-rated general health were less likely to be physically active. No relationship between psychological distress and physical activity was found for men. Women with high levels of psychological distress were less likely to be physically active. Conclusion Multimorbidity was not associated with physical activity levels in either sex, when age, education, income, and employment factors were controlled for. Long-term limitations on activity and poor-to-average self-rated general health seem related to a reduction in physical activity levels for both sexes, whereas psychological distress was associated with a reduction in physical activity levels only among women. Longitudinal studies using a comorbidity or multimorbidity index to account for severity of the chronic diseases are needed to replicate the results of this exploratory study.